Fresh-cut fruits and vegetables - Lamikanra, Olusola (CRC Press LLC, 2011)
Fresh-cut Fruits and Vegetables: Science, Technology, and Market provides a comprehensive reference source for the emerging fresh-cut fruits and vegetables industry. It focuses on the unique biochemical, physiological, microbiological, and quality changes in fresh-cut processing and storage and on the distinct equipment design, packaging requirements, production economics, and marketing considerations for fresh-cut products. Based on the extensive research in this area during the past 10 years, this reference is the first to cover the complete spectrum of science, technology, and marketing issues related to this field, including production, processing, physiology, biochemistry, microbiology, safety, engineering, sensory, biotechnology, and economics.ABOUT THE EDITOR:Olusola Lamikanra, Ph.D., is a Research Chemist and Lead Scientist at the U.S. Department of Agriculture, Agricultural Research Service, Southern Regional Research Center, New Orleans, Louisiana. He received his B.S. degree from the University of Lagos, Nigeria, and his Ph.D. from the University of Leeds, England. He was Professor in the Division of Agricultural Sciences and Director of the Center for Viticultural Science and Small Farm Development at Florida A&M University, Tallahassee. Dr. Lamikanra is the author of more than 100 publications.